2017
DOI: 10.1177/0042085917690205
|View full text |Cite
|
Sign up to set email alerts
|

Real or Ideal? A Narrative Literature Review Addressing White Privilege in Teacher Education

Abstract: A narrative literature review was conducted to examine how researchers address the concept of White privilege in teacher education using critical race theory. A Boolean search revealed 26 articles met criteria for inclusion. Findings show most researchers ( n = 15, 55%) investigated perceptions of White privilege within individual multicultural education courses and not comprehensively at the teacher education program level. Many White preservice teachers had difficulty connecting race-based privilege with sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Teachers who lack an understanding of systemic oppression in relation to race-based privilege may not have the capacity to work with educational researchers of P-12 urban schools to develop phronetic knowledge. Bennett, Driver, and Trent (2017) completed a narrative literature review addressing White privilege in teacher education and found that only one researcher (Page, 2010) explained the concept was addressed within multiple, recursive courses in her teacher education program. The majority of researchers who addressed the concept of White privilege in teacher education completed studies within single multicultural or diversity education courses (Bennett et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Teachers who lack an understanding of systemic oppression in relation to race-based privilege may not have the capacity to work with educational researchers of P-12 urban schools to develop phronetic knowledge. Bennett, Driver, and Trent (2017) completed a narrative literature review addressing White privilege in teacher education and found that only one researcher (Page, 2010) explained the concept was addressed within multiple, recursive courses in her teacher education program. The majority of researchers who addressed the concept of White privilege in teacher education completed studies within single multicultural or diversity education courses (Bennett et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Taken further, race-based data is important for employers, nursing associations and regulatory bodies to monitor and to aspire to attain equity in ethnicity demographics. Similarly, changes in the curricula should include concepts like cultural humility and White privilege to increase learners' knowledge about racism and to stop the perpetuation of it in academic and health institutions (Bennett et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Nursing schools should prepare undergraduate students to care for patients of all colors and races. Undergraduate students are taught to provide patients and their families with culturally safe care regardless of race, gender, culture or socioeconomic status (Bennett et al, 2020). However, during pathophysiology labs, nursing students are not exposed to manikins of color.…”
Section: Sub-theme Of Mentoring Programsmentioning
confidence: 99%